Peningkatan Teknologi Interaktif terhadap Pengembangan Sosial dan Emosional Pendidikan Anak Usia Dini (PAUD) - Victor Asido Elyakim P; Aliya Firanti; Lulu Hidayah Harahap; Mustika Almuthi Mawardani; Dermawan Perangin-angin (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
This activity aims to explore the influence of interactive technology on early childhood social and emotional development in early childhood education (ECED) settings. Interactive technologies such as tablets, learning apps and game-based educational devices are increasingly common in ECE classrooms. However, their impact on children's social and emotional development is still debated. This study used a quantitative survey approach with 50 children aged 4-6 years in ECD centers who had been using interactive technology for 6 months. The results of this activity show that interactive technology can have a positive influence on the development of children's social and emotional skills, provided that its use is directed and accompanied by teachers and parents. Children with moderate exposure to interactive technology showed improvements in their ability to interact with peers, as well as better emotional development in coping with frustration and understanding the feelings of others. However, there are also indications that excessive unaccompanied use may inhibit direct social interaction. Therefore, it is important to maintain a balance in the use of interactive technology in ECD to support children's optimal development.